(untitled) (Journal of Bangladesh Academy of Sciences, 2010)
Results of the energy intensity and overall energetic efficiency show that total energy output increased from 69.87 to 82.08 GJha-1, with increasing commercial energy input from 17.94 to 27.10 GJha-1 during 1990 to 2005. The corresponding increase in energy intensity was 45.67 to 54.47 MJ/US(2000). Energetic efficiency, calculated as the ratio of total output to input for different crops, using weight factor, decreased from 3.97 to 3.03. The energetic efficiency declines with increasing energy input, and the result indicates that input energy increases faster compared to energy output. The mechanization index increased from 64 to 78%. However, the main goal being maximization of the output per unit agricultural land, the estimated change in efficiency with increasing input can play an important role in choosing the appropriate input for optimum output. Key words: Energy intensity; Productivity; Agriculture DOI: 10.3329/jbas.v34i1.5492 Journal of Bangladesh Academy of Sciences, Vol.34, No.1, 59-70, 2010